Theoretical aspects and methods of the parameters identification of the electric traction system devices. The instantaneous powers method; series connection of elements - Mishchenko, T. M. (Science and Transport Progress, 2012)
Introduction: By means of the mathematical or computer (imitating) modeling the emergency, especially stochastic, transient electromagnetic and / or electro energetic processes in the electric traction system of the alternating current should be investigated. It allows expanding the research opportunities, as well as simplifying and reducing the actual testing, because it permits the wide variation of values and parameters reality of the elements of electric power circuits in the traction system without considerable material costs. Purpose: For this purpose the mathematical model of the nonlinear dynamical system "traction substation – electric traction network – electric rolling stock» as a passive two-terminal network with the given input voltage and input current is proposed. Task: The identification problem of the device under study, therefore the two-terminal network, is the determination electrical parameters (active resistance to inductance and capacity) of the passive elements, which substitute the two-terminal network. The scheme of its substitution looks like the series connection of passive elements. Methodology: The method of solving this problem for the passive two-terminal network in the traction mode with alternating, nonsinusoidal, deterministic periodic input voltage and input current is proposed. The calculations are executed for the electric locomotives DS3 and 2ES5K. Results: The results for the parameters can be applied in the further calculations of the more complex electric traction systems of the alternating current.